Evaluating Thyroid Function in Paediatric Nephrotic Syndrome in a Tertiary Care Hospital of Northern India: A Case-control Study - Koushal Kumar Khajuria; Ashima Badyal (JCDR Research and Publications Pvt. Ltd., 2022)
Introduction: Nephrotic Syndrome (NS) is a glomerular disease characterized by oedema, hypoalbuminemia and substantial proteinuria, which includes loss of thyroxine binding globulin and thyroid hormones, often resulting in subclinical or overt hypothyroidism. Studies reporting on the relationship between NS and thyroid dysfunction elude consensus. Aim: To evaluate Triiodothyronine (T3), Thyroxine (T4) and Thyroid Stimulating Hormone (TSH), and lipid levels to identify clinical predictors of thyroid dysfunction in paediatric cases of NS. Materials and Methods: A hospital based case control study was undertaken on 100 children, attending to paediatric nephrology clinic, from October 2020 to March 2021.Patients were divided into two groups: 50 cases under various stages of nephrotic syndrome, and 50 healthy controls in the age group of 1 to 18 years, of either gender. Investigations on Serum creatinine, haemoglobin, white blood cell count, platelet count, Serum T3, T4, TSH, and blood lipids like: Triglyceride (TG), Total Cholesterol (TC) and Low Density Lipoprotein (LDL), were performed on all the children, and compared for analysis of corresponding data of cases and controls. Statistical analysis was carried out using ANOVA test. Results: Mean T3 value in the case group was 117±63 ng/ dL, and in control was176±95 ng/dL (p=0.104). Mean T4 value among the case group (9.9±5.1 µg/dL) was significantly lower than that of controls (14.2±8.4 µg/dL) (p=0.016). The difference of TSH levels in the case group was 3.8±2.9 µIU/mL, and control was 2.5±2.2 µIU/mL (p<0.001). Hypothyroidism was observed in 9 (45%) children with first episode, 7 (53.84%) in remission, and 6 (60%) relapsed patients. Conclusion: Urinary losses of binding proteins such as Thyroxine Binding Globulin (TBG), transthyretin or prealbumin and albumin, may have caused lower levels of T3 and T4 and higher value of TSH. T3, T4 and TSH are important clinical predictors of thyroid dysfunction in patients with NS, therefore hypothyroidism should be investigated in all children with nephrotic syndrome.